Study on the Dispatching of Key Reservoirs in the Xijiang River Basin for Saltwater Resistance and Freshwater Supplement - LIU Xia; BAI Tao; WU Yunchen; HUANG Qiang (Renmin Zhujiang)
The saltwater intrusion in the Pearl River Delta has caused huge economic losses andsocial impacts to the surrounding areas. It is extremely urgent to reduce the adverse effects ofthe saltwater intrusion. Taking the eight key reservoirs in the Xijiang River Basin as theresearch object, this paper formulates the real-time dispatching simulation schemes of singlereservoir, two reservoirs and eight reservoirs in dry season respectively, and aiming at the low-water conditions of 95% and 99% incoming water frequency, establishes and applies the real-timedispatching simulation model of key reservoirs in the Xijiang River Basin to meet the saltwaterresistance and freshwater supplement demand of Wuzhou section at the downstream of Xijiang RiverBasin. The results show that: ① In the case of single-reservoir dispatching, and in the 95%incoming water scenario, Tianyi, Guangzhao, Longtan and Yantan reservoirs can meet the saltwaterresistance demand of the Wuzhou section. In the 99% incoming water scenario, only Tianyi andLongtan reservoirs can meet the saltwater resistance demand; ② The joint dispatching of tworeservoirs and seven reservoirs under different incoming water can meet the target of saltwaterresistance and freshwater supplement, and the water level of Longtan drops at the most flattrend; ③ In the process of saltwater resistance and freshwater supplement, the priority of allreservoirs is: Longtan, Tianyi, Yantan, Guangzhao, Xijin, Baise. The research results haveimportant theoretical significance for reducing the impact of salt tides in the Pearl River Delta,and provide an important reference for the subsequent real-time optimal dispatching of the keyreservoirs in the Xijiang River Basin.